2017
DOI: 10.1002/jbt.21936
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of mesenchymal stem cells on an experimentally induced model for multiple sclerosis in mice

Abstract: Multiple sclerosis (MS) is a chronic autoimmune demyelinating neurodegenerative central nervous system disorder. The aim of the present study was to investigate the prophylactic effect exerted by the one-time intraperitoneal injection of mesenchymal stem cells (MSCs) 1 × 10 and 14-day intraperitoneal injection of methylprednisolone (MP) 40 mg/kg in an experimental autoimmune encephalomyelitis (EAE). EAE was induced by intradermal injection of rat spinal cord homogenate with complete Freund's adjuvant in Swiss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Furthermore, MSCs also suppressed Th1 polarization directly, via secretion of TSG-6 [101]. Immunomodulation of the Th1-Th17 axis by MSC therapy has also been reported in numerous animal models of MS, which accompanied reduced expression of pro-inflammatory cytokines in the brain [102,103], diminished inflammatory infiltrates in the brain [102,104] and spinal cord [105], and improved motor function [102,105]. Interestingly, some of these studies suggest MSC-induced immunomodulation can cross species, as IV administration of EVs derived from human MSC lowered plasmatic levels of Th1-and Th17-related cytokines, and improved clinical outcomes [104,105].…”
Section: Immunomodulatory Effects Of Mscs In Preclinical Models Of Thmentioning
confidence: 90%
“…Furthermore, MSCs also suppressed Th1 polarization directly, via secretion of TSG-6 [101]. Immunomodulation of the Th1-Th17 axis by MSC therapy has also been reported in numerous animal models of MS, which accompanied reduced expression of pro-inflammatory cytokines in the brain [102,103], diminished inflammatory infiltrates in the brain [102,104] and spinal cord [105], and improved motor function [102,105]. Interestingly, some of these studies suggest MSC-induced immunomodulation can cross species, as IV administration of EVs derived from human MSC lowered plasmatic levels of Th1-and Th17-related cytokines, and improved clinical outcomes [104,105].…”
Section: Immunomodulatory Effects Of Mscs In Preclinical Models Of Thmentioning
confidence: 90%
“…43 This is reflected in our study as the model group showed rise in the levels of these parameters as well as MPO levels which is an enzyme correlated with the disease severity. 44 Levels of NF-kB p65 subunit which has a role in driving the inflammatory immune responses were also elevated in this group post induction. 45 In contrast, BDNF levels were reduced as it is negatively affected by the circulating cytokines as well as the decrease in the levels of TGF-β, CNP, IL-4 and Olig-1.…”
Section: Discussionmentioning
confidence: 73%
“…Existen diferentes protocolos para inducir la enfermedad pero los más utilizados se basan en la inmunización del animal con un autoantígeno para inducir la activación de sus células T reactivas (EAE activa) o bien en la transferencia de células T autorreactivas a un animal naïve (EAE pasiva) 6,20 . Para provocar la EAE de manera activa se necesita un adyuvante, siendo el más utilizado el Complete Freund's Adjuvant 21 , el cual produce una lenta liberación del antígeno procedente del inóculo 2 además de utilizar alguna especie de micobacteria, normalmente Bordetella pertussis, la cual provoca una expansión clonal de linfocitos T autorreactivos 6 , potenciando de esta manera las manifestaciones típicas de EM al favorecer la respuesta inmune humoral 22 . Aunque la EAE ha sido utilizada para estudiar los mecanismos relacionados con la neuroinflamación y la respuesta inmune, también ha sido utilizada para el estudio de los procesos de desmielinización y remielinización 19 .…”
Section: La Encefalitis Alérgica Experimentalunclassified